Effects of a phytobiotic-based additive on the growth, hepatopancreas health, intestinal microbiota, and Vibrio parahaemolyticus resistance of Pacific white shrimp, Litopenaeus vannamei - Ma, Qiang; Zhao, Guiping; Liu, Jiahao; Chen, I-Tung; Wei, Yuliang; Liang, Mengqing; Dai, Ping; Nuez-Ortin, Waldo G.; Xu, Houguo (Frontiers in Immunology, 2024)
Vibrio genus is a common pathogen in aquaculture, and causes acute hepatopancreatic necrosis disease (AHPND) and massive mortality of shrimp. Many studies have suggested that single functional ingredient such as plant extract or organic acid can reduce the dependence on antibiotics and promote growth and immunity of aquatic animals. In this study, we evaluated the effects a phytobiotic-based compound additive (Sanacore® GM, SNGM), which had a successful trajectory of commercial application in fish farming. However, its effects on the hepatopancreas health and intestinal microbiota of shrimp after Vibrio challenge have not been well evaluated. In the present study, Pacific white shrimp were fed diets with or without supplementation of SNGM, and the SNGM grades were 0 (CON), 3 (SNGM3), and 5 (SNGM5) g/kg diet. The feed trial lasted 60 days, after which a Vibrio parahaemolyticus challenge was performed. The results showed that compared to the CON group, both the SNGM3 and SNGM5 groups had significantly higher weight gain and lower feed conversion ratio, as well as higher survival after Vibrio parahaemolyticus challenge. In the growth trail, the SNGM3 significantly increased the total protein, albumin concentration and acid phosphatase activity in hemolymph compared to the CON group. In the challenge experiment, the SNGM3 and SNGM5 increased the albumin and glucose contents, as well as the activities of phenoloxidase, lysozyme, alkaline phosphatase and superoxide dismutase in hemolymph. Both the SNGM3 and SNGM5 improved the morphology of hepatopancreas and intestine. The SNGM5 alleviated the gut microbiota dysbiosis induced by Vibrio infection by increasing the potential probiotic bacterium abundance (Shewanella) and decreasing the potential pathogenic bacteria abundance (Vibrio, Photobacteriuma, Pseudoalteromonas and Candidatus_Bacilloplasma). In conclusion, dietary the phytobiotic-based additive at 3 g/kg level increased the growth and Vibrio parahaemolyticus resistance of Pacific white shrimp by promoting immune-related enzyme activities, morphological structure of hepatopancreas and intestine, and intestinal microbiota composition.